Model of iceberg drift and decay including breakup - England, Mark; Wagner, Till (U.S. Antarctic Program (USAP) Data Center, 2022)
Because of difficulties in adequately simulating their breakup, large Antarctic icebergs to date have either not been represented in models or represented but with no breakup scheme such that they consistently survive too long and travel too far compared with observations. Here, we introduce a representation of iceberg fracturing using a breakup scheme based on the “footloose mechanism.” We optimize the parameters of this breakup scheme by forcing the iceberg model with an ocean state estimate and comparing the modeled iceberg trajectories and areas with the Antarctic Iceberg Tracking Database. We show that including large icebergs and a representation of their breakup substantially affects the iceberg meltwater distribution, with implications for the circulation and stratification of the Southern Ocean. This data link includes the model developed for the study, including a link to the forcing fields needed to replicate the model results.